SNOW WHITE’S TRAITS THAT ARE AGAINST THE IDEA OF PATRIARCHY REFLECTED IN MIRROR MIRROR MOVIE - JANNAH, ROUDATUL (Jurnal Ilmiah Mahasiswa FIB, 2013)
Patriarchal society puts a man in a dominant position which has more power than woman. Anything that has been defined by the man has to be followed by the wife and children. If theydo not obey the rules, they will be seen as a rebellious person who will be degraded by society.This system does not support women so there is a feminist movement to reject it.  To analyse Mirror Mirror movie, the writer applies feminism theory which focus onpatriarchy and movie study. This study uses qualitative approach in analyzing this movie. The writer applies movie study to show the actions which are done by Snow White usingpictures, dialogues, and narrations to strengthen it. The writer’s research is different from threeothers researchers in her previous study because she combines the theory into movie study whichmakes this research more compatible and more interesting to read.   From the analysis, the result of the study shows that there are five traits of Snow White toagainst the idea of patriarchy. The traits are her intelligence is become a problem solver, anegotiator, and a creative woman; her rebellious is rebel someone inside and outside theKingdom; her independence is handle everything which comes to her; her courageous is face thefear, and her leadership is become a leader of men.  The writer suggests that the literary criticism of Mirror Mirror Movie can be conductedmore comprehensively using different theories like Postcolonial theory or Marxism theory. Thewriter suggests to observe about another women characters in this movie so the researcher canget new insights form the study. Keywords: patriarchy, feminism, movie, Snow White